Prognostic Histopathological and Molecular Markers on Prostate Cancer Needle-Biopsies: A Review. (27th August 2014) - Hoogland, A. Marije; Kweldam, Charlotte F.; Leenders, Geert J. L. H. van
Abstract : Prostate cancer is diverse in clinical presentation, histopathological tumor growth patterns, and survival. Therefore, individual assessment of a tumor's aggressive potential is crucial for clinical decision-making in men with prostate cancer. To date a large number of prognostic markers for prostate cancer have been described, most of them based on radical prostatectomy specimens. However, in order to affect clinical decision-making, validation of respective markers in pretreatment diagnostic needle-biopsies is essential. Here, we discuss established and promising histopathological and molecular parameters in diagnostic needle-biopsies.